(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
Persuasive strategies are formed by the combination of three dimensions: language, culture, and rhetorical devices. This paper is a stylistic study based on Johnstone’s model of persuasion, which is applied to "A Fishing Excursion " by Guy de Maupassant, to examine the three linguistic strategies of the model throughout the story. The study is dedicated to showing a detailed analysis of the strategies of persuasion in the story and interpreting the significance of each to the progress of the plot. As well as shedding light on the rhetorical patterns that are used in the story. Besides, the study hypothesizes that the selected model applies to Maupassant’s "A Fishing Excursion," and it is significant to reveal the linguistic strategies of persuasion. Therefore, comprehensive tables and illustrative figures are provided based on the statistical data. The results show that some stylistic markers appear to be specific to the writer’s style in the selected text.